The Nellix™ EndoVascular sealing system in patients with abdominal aortic aneurysms in conjunction with iliac artery occlusive disease. (April 2017) - van Sterkenburg, Steven MM; van den Ham, Leo H; Smeets, Luuk; Lardenoije, Jan-Willem; Reijnen, Michel MPJ
Introduction: Concomitant abdominal aortic aneurysm formation and aortoiliac occlusive disease is a challenging combination, often requiring open reconstructive surgery. In this study, we have assessed a single center experience of the Nellix EndoVascular Aneurysm Sealing System in the treatment of an abdominal aortic aneurysm in conjunction with iliac artery occlusive disease. Methods: Retrospectively case files of patients treated with Nellix EndoVascular Aneurysm Sealing System in a single center were reviewed. The primary endpoints of the study were the technical success of Nellix EndoVascular Aneurysm Sealing System in patients with coincidental iliac artery occlusive disease and the successful exclusion of the aneurysm during follow-up. Results: Of the 96 patients that were treated with Nellix EndoVascular Aneurysm Sealing System, five were identified that had an abdominal aortic aneurysm in conjunction with iliac artery occlusive disease. Treated patients had either unilateral (n = 4) or bilateral (n = 1) common iliac artery occlusive disease varying from 70% stenosis to complete occlusions. The lesion length varied from 5 to 50 mm and in two cases it involved an occluded bare metal stent. The indication for surgery was the abdominal aortic aneurysm in all patients, including three also suffering from claudication. In all patients the iliac artery occlusive disease was pretreated with balloon-expandable covered stents. Technical success was achieved in all five patients. After a median follow-up of nine months all stents were patent with no signs of endoleak and stable aneurysm diameters. All patients were free of intermittent claudication or ischemic wounds. Conclusion: Nellix EndoVascular Aneurysm Sealing System seems feasible and safe in patients with a combination of abdominal aortic aneurysm and iliac artery occlusive disease.